Characteristics of new cement-based thermoelectric composites for low-temperature applications. (18th October 2021) - Liu, Xiaoli; Qu, Ming; Nguyen, Alan Phong Tran; Dilley, Neil R.; Yazawa, Kazuaki
Highlights: A new thermoelectric cement composite enhanced by graphite and MnO2. Simultaneous measurement of thermoelectric properties for cement composites. Impacts of dry mixing and wet mixing on samples' TE performance. Impacts of additives' concentrations and electrical contact resistance. Abstract: Thermoelectric cement, the mixture of cement and thermoelectric additives, can convert energy between thermal and electrical forms due to the thermoelectric additives. Potentially, they could be the material for building envelopes to harvest waste heat and/or provide space cooling or heating. When there is a significant difference between indoor and outdoor temperatures, the thermoelectric cement can generate electricity using the temperature gradient. And the same material can cool or heat building space via building envelopes with an electrical input. The research aimed to identify and characterize thermoelectric cement candidates for building envelope applications. The additives used in the studied thermoelectric cement candidates include graphite and MnO2 . Except for the additives, the study also explored the impact of the two different fabrication methods: wet-mixing and dry-mixing on thermoelectric performance. The images of TE cement candidates taken by scanning electron microscopy and energy dispersive X-ray microscopy visualized the morphology and distribution of additives in the thermoelectric cement composites. The DynaCool Physical Properties Measurement System used in the study simultaneously measured the candidates' thermoelectric properties, including thermal conductivity, electrical conductivity, Seebeck coefficient, and Figure of merit ( ZT ). The test results showed that the thermoelectric cement with the additives of 10% (weight ratio) graphite and 5% MnO2 has the highest ZT of 6.2 × 10 −6 at 350 K. ZT of the thermoelectric cement is even higher to 10 −5 orders of magnitude when applying a four-probe electrical resistivity method to account for the contact resistance.